MORAL EDUCATION TO EMPOWER CONSCIENCE, MIND AND VOLITION TO IMPROVE THE QUALITY OF HUMAN BEINGS - Paulus Wahana (Sanata Dharma University Yogyakarta, 2018)
Human beings are the highest form of Gods creation among other creatures. Moral education is carried out to enable human beings to live up to their noble purpose of life as destined by God. In order to strive for their noble destiny, human beings have three spiritual powers that must be empowered and utilized in their lives, namely conscience, mind, and volition. In order for those powers to be useful optimally, they must be empowered. In order to empower conscience, it is necessary to cultivate silence in life so that we are able to listen to the gentle whisper of conscience which leads to a good life as the purpose in the journey of life. To prevent the conscience from straying, it needs to have a moral compass which would be the basis to determine the next steps. Furthermore, one should have clear mind to determine the ways, steps, means, and directions to arrive at the expected goal. Finally, in order to realize the qualified life, which has been determined to be done, human beings have willpower to follow up. To determine and decide something, human beings must be courageous to take action. In order to be courageous to take action, we need to have a strong consideration that what we are doing is good and right. Thus, we will dare to be held accountable for any outcomes of the actions we have taken as right and just. That is, essentially, the true human destiny, namely to strive for goodness and truth.DOI:https://doi.org/10.24071/ijiet.2018.020109